2009
DOI: 10.1111/j.1600-0854.2009.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein‐2 Interaction with Arrestin Regulates GPCR Recycling and Apoptosis

Abstract: G protein-coupled receptors (GPCRs) are integral to cellular function in nearly all physiologic and many pathologic processes. GPCR signaling represents an intricate balance between receptor activation, inactivation (desensitization, internalization and degradation) and resensitization (recycling and de novo synthesis). Complex formation between phosphorylated GPCRs, arrestins and an ever-increasing number of effector molecules is known to regulate cellular function. Previous studies have demonstrated that, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 60 publications
6
48
2
Order By: Relevance
“…These data suggest that arrestin-3 inhibits ␤1AR recycling through the TGN-associated mechanism. This finding is at odds with prior work, which has shown that arrestin-2 and -3 increase the recycling of the formyl peptide receptor (26,27), and may suggest that arrestins regulate the recycling of GPCRs in a receptor-specific fashion.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These data suggest that arrestin-3 inhibits ␤1AR recycling through the TGN-associated mechanism. This finding is at odds with prior work, which has shown that arrestin-2 and -3 increase the recycling of the formyl peptide receptor (26,27), and may suggest that arrestins regulate the recycling of GPCRs in a receptor-specific fashion.…”
Section: Discussioncontrasting
confidence: 56%
“…It is noteworthy that endocytosed CC chemokine receptor 5 was initially thought to accumulate in the perinuclear region (9), but the TGN was identified later as the perinuclear organelle where CC chemokine receptor 5 retrotranslocated (9). Interestingly, other GPCRs such as ␤2AR (19), CXCR2 (C-X-C chemokine receptor type 2 (24), somatostatin receptor 3 (25), N-formyl peptide receptor (26), and vasopressin 2A receptor (5) also accumulate in the perinuclear area after endocytosis. Thus, it is possible that these receptors might also return to the TGN after desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…AP-2 has been shown to associate with the N-formyl peptide receptor, a GPCR, on perinuclear endosomes via ␤-arrestins to facilitate recycling (33). Intriguingly, however, depletion of endogenous AP-2 resulted in the initiation of apoptosis induced by multiple GPCR-specific ligands.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AP-2 modulates RGS protein recruitment to G q protein in response to PAR1 activation and, thereby, provides an additional mode by which GPCR signaling can be regulated. Future studies will be important to determine whether other GPCRs that associate with AP-2, such as the N-formyl peptide receptor or thromboxane A2 receptor TP␤, are regulated similarly (33,39). The precise mechanism by which AP-2 affects RGS protein recruitment to G proteins remains unclear and is an important future pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the YETI motif does play a role in the trafficking of internalized Y 1 receptors. It was recently shown that AP-2 association with the N-formyl peptide receptor (FRP)-arrestin complex in perinuclear endosomes is required for recycling of this receptor [33]. Further work is thus necessary to determine whether indeed there is a direct interaction between the AP-2 complex and the full-length activated Y 1 receptor and whether this interaction influences the route of the receptor once internalized.…”
Section: Discussionmentioning
confidence: 99%